Herbicide-resistant weed biotypes in Ukraine - Schwartau, V.V.; Mykhalska, L.M. (Reports of the National Academy of Sciences of Ukraine, 2022)
In Ukraine, resistant to the action of herbicides — acetolactate synthase inhibitors of the imidazolinone class — imazapyr and imazamox biotypes of monocot Echinochloa crus-galli var. crus-galli, and dicot Amaranthus retroflexus, and Chenopodium album have been identified. Cross-resistance to herbicides: monocot to sulfonylurea (nicosulfuron), and triazole pyrimidines (penoxsulam); dicots to sulfonylurea foramsulfuron, iodosulfuronmethyl- sodium, thifensulfuron-methyl, tribenuron-methyl; to sulfonylaminocarbonyl triazolinone derivative — thiencarbazone-methyl; to t riazole pyrimidine derivatives — florasulam, and flumetsulam were established. The multiple resistance of Echinochloa crus-galli, Amaranthus retroflexus, and Chenopodium album to herbicides of the classes of glycine derivatives — glyphosate, monocot to graminicide pinoxaden, and dicot species to phenoxy carboxylic derivatives — 2,4-D, benzoic acid — dicamba; triketones — topramezone; diphenyl ethers — aclonifen have not been established. It was shown for the first time that herbicide compositions under the influence of the ammonium pool can increase the level of controlling resistant weed biotypes effectiveness. The identification of highly harmful ALS-resistant Echinochloa crus-galli, Amaranthus retroflexus, and Chenopodium album in the south and central part of the “grain belt” of Ukraine shows the limited effectiveness of weed control exclusively with herbicides with one mechanism of action and requires a significant revision of the principles of crop rotation formation and methods of weed control in the state to maintain high levels of profitability and productivity of agrophytocenoses. Solving these issues is urgent in order to preserve Ukraine’s potential as one of the guarantors of world food security.